2022
DOI: 10.3389/fvets.2022.915896
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cannabinoid Receptors in Keratinocytes of Healthy Dogs and Dogs With Atopic Dermatitis

Abstract: It is commonly accepted that some form of skin barrier dysfunction is present in canine atopic dermatitis (AD), one of the most common cutaneous pruritic inflammatory diseases of dogs. The impaired skin barrier function facilitates the penetration of allergens and subsequently stronger sensitization responses. The role of the endocannabinoid system (ECS) in the physiology and pathology of the skin is becoming increasingly established. It has been demonstrated that cannabinoid receptors are expressed in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…Sensory neurons expressing TRPA1-IR usually co-express TRPV1-IR ( 86 ). However, TRPA1 is also functionally expressed in skin cells, such as keratinocytes, MCs, macrophages, DCs, melanocytes, and endothelial cells ( 45 , 87 89 ). The observation of TRPA1-IR in the MCs of the AD-dogs was consistent with the findings of Oh et al ( 87 ) who showed TRPA1 in the MCs of AD lesions of humans and mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sensory neurons expressing TRPA1-IR usually co-express TRPV1-IR ( 86 ). However, TRPA1 is also functionally expressed in skin cells, such as keratinocytes, MCs, macrophages, DCs, melanocytes, and endothelial cells ( 45 , 87 89 ). The observation of TRPA1-IR in the MCs of the AD-dogs was consistent with the findings of Oh et al ( 87 ) who showed TRPA1 in the MCs of AD lesions of humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Eight client-owned dogs diagnosed with spontaneous AD, based on predefined diagnostic criteria ( 45 ) and on the exclusion of other causes of pruritus (flea bite, allergic dermatitis and adverse food reaction), were enrolled ( Table 1 ). Cutaneous samples were collected from the AD-dogs on which no treatment had been made in the previous 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations